Do psychosocial factors moderate the relation between testosterone and female sexual desire? The Role of Interoception, Alexithymia, Defense Mechanisms, and Relationship Status - Costa, Rui Miguel (2018)
Objectives Low sexual desire is a common complaint among women in the reproductive years. There is controversy regarding the relationship between testosterone (T) and female desire, but there is also lack of research on moderators. Lack of awareness of effects of T on emotions and bodily sensations might interfere with the subjective experience of desire. Moreover, T appears to be more important for searching and competing for partners than for long-term pair bonding. Therefore, we examined if interoception, alexithymia, maladaptive psychological defenses, and relationship status, moderated the relationship between salivary T and female desire. Methods One hundred sixty eight Portuguese women of reproductive age completed the desire dimension of the Female Sexual Function Index, the Toronto Alexithymia Scale (TAS-20), and the Defense Style Questionnaire (DSQ-40). Interoception was determined by a heartbeat detection task. Participants reported if they had a regular sexual partner. Luminescence immunoassays were used to determine salivary T. Results Three multiple regressions models revealed that, among unpartnered women, higher desire was predicted by the combinations of 1) higher T and lesser alexithymia, 2) higher T and less use of maladaptive defenses, 3) higher T and greater interoception. For partnered women, neither T nor the interactions of T with indices of emotional and bodily awareness predicted desire. Conclusions These findings provide preliminary evidence that T is more important for the desire of unpartnered women, and that lack of conscious awareness of emotions and bodily sensations interferes with the effects of T on the subjective experience of desire.